Modeling the growth, yield and N dynamics of wheat for decoding the tillage and nitrogen nexus in 8-years long-term conservation agriculture based maize-wheat system - Kumar, Kamlesh; Parihar, C. M.; Sena, D. R.; Godara, Samarth; Patra, Kiranmoy; Sarkar, Ayan; Reddy, K. Srikanth; Ghasal, P. C.; Bharadwaj, Sneha; Meena, A. L.; Das, T. K.; Jat, S. L.; et al. (Frontiers in Sustainable Food Systems, 2024)
Agricultural field experiments are costly and time-consuming, and their site-specific nature limits their ability to capture spatial and temporal variability. This hinders the transfer of crop management information across different locations, impeding effective agricultural decisionmaking. Further, accurate estimates of the benefits and risks of alternative crop and nutrient management options are crucial for effective decision-making in agriculture.Synthesis CERES-Wheat model to simulate crop growth, yield, and nitrogen dynamics in a longterm conservation agriculture (CA) based wheat system. The study aimed to calibrate the model using data from a field experiment conducted during the 2019-20-2020-21 growing seasons and validate it with independent data from the year 2021-22.Crop simulation models, such as the Crop Environment Resource Synthesis CERES-Wheat (DSSAT v 4.8), may provide valuable insights into crop growth and nitrogen dynamics, enabling decision makers to understand and manage production risk more effectively.Therefore the present study employed the CERES-Wheat (DSSAT v 4.8) model and calibrated it using field data, including plant phenological phases, leaf area index, aboveground biomass, and grain yield from the 2019-20-2020-21 growing seasons. An independent dataset from the year 2021-22 was used for model validation. The model was used to investigate the relationship between growing degree days (GDD), temperature, nitrate and ammonical concentration in soil, and nitrogen uptake by the crop. Additionally, the study explored the impact of contrasting tillage practices and fertilizer nitrogen management options on wheat yields. The experimental site is